Television-watching habits of children in kindergartens in a village of Somogy county - Pavlényiné Boza, Anita; Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2014)
Television-watching habits of children in kindergartens in a village of Somogy county Children at this young age, when they attend kindergarten, do not yet have a developed system of values; they cannot make difference between reality and the vision that they see on television. However, many of nowaday’s children spend the majority of their free time in front of the television sets, and just watch what they find. The main topic of this research is to discover the television-watching habits of the kindergarten-aged community of a small village in Somogy county. The work seeks to answer the questions how much the parents control the television-watching activity of their children; whether they are aware how much their children watches television and which programmes; and if they recognize the possible positive or negative effects of this activity.
Keywords: kindergarten; education; television; personal development